HLA-II Alleles Influence Physical and Behavioral Responses to a Whey Allergen in a Transgenic Mouse Model of Cow's Milk Allergy - Germundson, Danielle L.; Nookala, Suba; Smith, Nicholas A.; Warda, Yassmine; Nagamoto-Combs, Kumi (Frontiers in Allergy, 2022)
The symptoms of food allergies vary significantly between individuals, likely due to genetic determinants. In humans, allergy development is initiated by antigen-presenting cells via class II human leukocyte antigen (HLA-II). The HLA-II gene is highly polymorphic, and its allelic variance is thought to influence the susceptibility of individuals to a particular allergen. However, whether antigen presentation by different HLA-II variants contributes to symptom variation is not clear. We hypothesized that HLA-II allelic variance affects symptom phenotypes, including immediate physical reactions and delayed behavioral changes, in individuals with food hypersensitivity. To test our hypothesis, male and female mice of three transgenic strains expressing an HLA-II variant, DR3, DR15, or DQ8, were used to establish a cow’s milk allergy model. Mice were sensitized to a bovine whey allergen, β-lactoglobulin (BLG; Bos d 5), weekly for 5 weeks, followed by an acute oral allergen challenge. At 30 min post-challenge, BLG-sensitized DR3 mice showed moderate to severe anaphylaxis resulting in perioral redness, swelling, and death. In contrast, DQ8 and DR15 mice were generally asymptomatic. The production of allergen-specific immunoglobulins was also HLA- and sex-dependent. Both male and female DR3 and female DR15 mice significantly increased BLG-specific IgE production, while robust elevation in BLG-specific IgG1 was observed in sensitized DQ8 mice of both sexes and, to a lesser extent, in DR15 males. Furthermore, BLG-sensitized DR15 mice showed sex-specific behavior changes, with males exhibiting mobility changes and anxiety-like behavior and females showing spatial memory impairment. When splenocytes from transgenic mice were stimulated in vitro with BLG, phenotypes of immune cells were HLA- and sex-specific, further underscoring the influence of HLA-II on immune responses. Our results support that HLA-II alleles influence behavioral responses in addition to immune and physical reactions of food allergy, suggesting that certain HLA-II variants may predispose individuals to food-allergy-associated behavioral changes.